k-smoothness: an answer to an open problem - Wójcik, Paweł (MATHEMATICA SCANDINAVICA, 2018)
The aim of this paper is to characterize the k-smooth points of the closed unit ball of K(H_1;H_2). In this paper we also answer a question posed by A. Saleh Hamarsheh in 2015.